2019
DOI: 10.7567/1347-4065/aafe73
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dielectric barrier discharges with water in correlation to productions of OH and H2O2 in gas and liquid phases

Abstract: Using several types of dielectric barrier discharges, we studied the production mechanisms of H2O2 molecules in gas and liquid phases. Water vapor was supplied by a water bubbler in a gas-feed line or vaporization of water filling a lower electrode well. Densities of OH radicals were measured by optical emission and laser-induced fluorescence spectroscopic methods and correlated with the H2O2 production in gas phase. The energy yield of H2O2 obtained in the gas-phase synthesis with the supply of water vapor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 86 publications
(196 reference statements)
2
10
1
Order By: Relevance
“…The presented value is only estimative and does not reflect the in situ measurement of hydrogen peroxide production. The most probable hydrogen peroxide production is water molecule splitting, OH radical reactions during the plasma activation, and the preservation by effective absorption into the water [ 1 , 2 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presented value is only estimative and does not reflect the in situ measurement of hydrogen peroxide production. The most probable hydrogen peroxide production is water molecule splitting, OH radical reactions during the plasma activation, and the preservation by effective absorption into the water [ 1 , 2 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inactivation of bacteria is dependent on biofilm thickness, the penetration depth of active particles and induced secondary products. Thus, hydrogen peroxide and OH radicals are very important in the process [ 2 , 11 , 37 ]. To test the effect of plasma-activated media compared to water vapor, we exposed the S. aureus biofilm to condensates and physiological solution (control sample).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, under humid conditions (e.g. discharge in the presence of water vapour or humid samples), an additional source of UV photons arises owing to the OH radical [227][228][229][230][231]. However, the fluency of photons to which the treated samples may be effectively exposed considerably depends on both discharge and exposure geometries.…”
Section: Radiationmentioning
confidence: 99%
“…Later, some kind of a modified viewpoint was proposed, that is, the H 2 O 2aq is formed inside the liquid by the recombination of the OH aq generated in situ in the liquid phase by positive ion bombardment [73][74][75][76][77][78] or by ultraviolet (UV) and vacuum ultraviolet photolysis of water [79,80] (Equations ( 4), ( 5)). Several more recent research studies [81][82][83][84] suggested that gaseous H 2 O 2 is formed in the gaseous plasma by the combination of the OH g species and then a gas to liquid transfer of the gaseous H 2 O 2 (H 2 O 2g ) leads to the formation of the H 2 O 2aq (Equations ( 2), ( 6), (7)). Up to date, the exact mechanism of the H 2 O 2aq formation in the DC plasma-liquid system is still in dispute, although the consensus in these proposals is that the OH radicals are the building block of the H 2 O 2aq species.…”
mentioning
confidence: 99%